ANALISIS PERJANJIAN DENGAN SISTEM EMPLONG DI DESA SUNGAI RENGAS BERDASARKAN KATAGORI HUKUM AKAD PASAL 26-28 DAN PENAFSIRAN AKAD PASAL 48-55 KOMPILASI HUKUM EKONOMI SYARIAH - Aisyah, Siti; Fahmi, Moch. Riza; Wahyuni, Dwita (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2025)
The purpose of the research is to: (1) Understand the process of creating an emplong (profit-sharing) agreement in Sungai Rengas Village; (2) Analyze its provisions according to Articles 26-28 of KHES regarding contract categories; and (3) Interpret it according to Articles 48-55 of KHES concerning contract interpretation. The research method used is empirical, with data collection techniques through interviews and documentation. Data analysis is conducted descriptively through four stages: collection, reduction, presentation, and conclusion drawing. The research findings indicate that: first, the process of an emplong agreement begins with an initial approach between the landowner and the cultivator, followed by negotiation of terms (such as a 50:50 profit split), and concludes with an agreement. Second, based on Articles 26-28 of KHES, this agreement shares similarities with a lease contract (ijarah) as it involves the utilization of an object (land) and must fulfill the valid conditions and pillars in Islam. Third, the interpretation according to Article 48 of KHES emphasizes that the execution of the contract must align with the original intent and purpose of the agreement (maudhu' al-'aqd), not merely adhering to its formal wording. Thus, the essence of cooperation and fairness in profit-sharing serves as its fundamental basis.